New developed spectrophotometric method for simultaneous determination of salmeterol xinafoate and fluticasone propionate in bulk powder and Seritide® diskus inhalation - Ahmed Samir; Hesham Salem; Mohammad Abdelkawy (Bulletin of Faculty of Pharmacy Cairo University, 2012)
A new simple, accurate, precise, rapid and economical method was developed for the simultaneous determination of Salmeterol xinafoate and Fluticasone propionate in their binary mixture in bulk powder and Seritide diskus® inhalation. The new method depends on new calculations using the mixture’s absorbance at 225 and 256.5 nm where the absorptivity of Salmeterol xinafoate is double the absorptivity of Fluticasone propionate, while the content of Salmeterol xinafoate was determined by measuring the absolute value of the first derivative ultraviolet curves at 352 nm, without interference from Fluticasone propionate. The proposed method was validated and the results obtained by adopting the proposed method were statistically analyzed and compared with those obtained by reported methods.